2019
DOI: 10.1001/jamaneurol.2019.2167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Standard vs Intensive Blood Pressure Control on the Risk of Recurrent Stroke

Abstract: ; for the Recurrent Stroke Prevention Clinical Outcome (RESPECT) Study Group IMPORTANCE The Systolic Blood Pressure Intervention Trial (SPRINT) demonstrated that a systolic blood pressure (BP) target less than 120 mm Hg was superior to less than 140 mm Hg for preventing vascular events. This trial excluded patients with prior stroke; therefore, the ideal BP target for secondary stroke prevention remains unknown. OBJECTIVE To assess whether intensive BP control would achieve fewer recurrent strokes vs standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
108
1
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 19 publications
4
108
1
12
Order By: Relevance
“…[ 28 30 ] A previous systematic review showed that baseline blood pressure could affect the outcome of surgery, [ 31 ] and blood pressure control could lowering the risk of carotid revascularization. [ 32 ] Indeed, blood pressure control to lower the risk of recurrent of stroke has gained increasing attention in recent years. [ 32 ] Both hyperglycemia and hypertension are important components of MetS, and could impact micro-perfusion of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 30 ] A previous systematic review showed that baseline blood pressure could affect the outcome of surgery, [ 31 ] and blood pressure control could lowering the risk of carotid revascularization. [ 32 ] Indeed, blood pressure control to lower the risk of recurrent of stroke has gained increasing attention in recent years. [ 32 ] Both hyperglycemia and hypertension are important components of MetS, and could impact micro-perfusion of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic pressure above 140 mmHg [31] Diastolic pressure above 100 mmHg Peripheral saturation below 90% At the request of the volunteer for excessive fatigue or pain…”
Section: Intervention and Controlmentioning
confidence: 99%
“…На сегодняшний день проведены 6 крупных РКИ по изучению целевых уровней АД у пациентов с АГ и церебральными событиями в анамнезе: The Secondary Prevention of Small Subcortical Strokes (SPS3) [5], Рerindopril protection against recurrent stroke study (PROGRESS) [3], Prevention Regimen For Effectively Avoiding Second Strokes (PRoFESS) [6], Post-stroke Antihypertensive Treatment Study (PATS) [4], Morbidity and Mortality After Stroke, Eprosartan Compared With Nitrendipine for Secondary Prevention study (MOSES) [7] и Recurrent Stroke Prevention Clinical Outcome Study (RESPECT) [8]. Дизайн этих исследований и характеристика включенных пациентов представлены в табл.…”
unclassified
“…[11] и 2019 г. [8]. В крупном РКИ SPS3 [5], в котором приняли участие 3020 пациентов (средний возраст 63 года) с перенесенным лакунарным инсультом (180 дней и менее перед рандомизацией), период наблюдения в среднем 3,7 года, показаны некоторые преимущества достижения целевого уровня САД<130 мм рт.…”
unclassified
See 1 more Smart Citation